Omega-3 fatty acids enhance the beneficial effect of BCAA supplementation on muscle function following eccentric contractions - Yosuke Tsuchiya; Kenichi Yanagimoto; Norihiko Sunagawa; Hisashi Ueda; Katsunori Tsuji; Eisuke Ochi (Taylor & Francis Group, 2022)
Background This study investigated the combined effect of branched-chain amino acids (BCAA) and fish oil (FO) on muscle damage caused by eccentric contractions (ECCs) of the elbow flexors, with a special focus on muscular function. Methods Twenty-nine untrained male participants were enrolled in this double-blind, placebo-controlled, parallel study. The participants were randomly assigned to the placebo (PL) group (n = 9), BCAA supplement group (n = 10), and BCAA+FO supplement group (n = 10). The BCAA+FO group consumed eicosapentaenoic acid (EPA) 600 mg and docosahexaenoic acid (DHA) 260 mg per day for 8 weeks, while the BCAA and BCAA+FO groups consumed 9.6 g per day for 3 days prior to and until 5 days after ECCs. Participants performed six sets of 10 ECCs at 100% maximal voluntary contraction (MVC) using dumbbells. Changes in MVC torque, range of motion (ROM), muscle soreness using visual analog scales, upper circumference, muscle thickness, echo intensity, and serum creatine kinase (CK) were assessed before, immediately after, and 1, 2, 3, and 5 days after ECCs. Results The MVC torque was significantly higher in the BCAA+FO group than in the PL group immediately after ECCs (p < 0.05) but not in the BCAA group. Both BCAA and BCAA+FO groups showed greater ROM and lower muscle soreness than the PL group (p < 0.05). CK was significantly lower in the BCAA group than in the PL group at 5 days after ECCs (p < 0.05). Conclusions This study reveals that supplementation with BCAA and FO may favorably impact immediate recovery of peak torque production. Alternatively, in comparison to PL group, BCAA supplementation favorably reduces creatine kinase.